THE EFFECT OF MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. ADI KARYA - Hayanuddin Safri; Zuriani Ritonga; Rahmi Rahmi; Sufitrayati Sufitrayati; Nelly Nelly (Jurnal Ekonomi, 2022)
PT Adi Karya is a company engaged in the contractor sector, which requires the expertise and ability of employees to be able to operate every task assigned by the company to its employees. With the intensity of the work being carried out, PT Adi Karya always wants its employees to have high motivation and satisfaction with the work done so that performance will increase. In accordance with the description above, the authors feel interested in conducting research entitled: "The Influence of Motivation and Job Satisfaction on Employee Performance at PT Adi Karya". The results of this research are that employee performance is influenced by motivation and job satisfaction simultaneously on employee performance by 52.7% and the remaining 47.3% is determined by other variables.